2011
DOI: 10.4103/0256-4947.87097
|View full text |Cite
|
Sign up to set email alerts
|

Influence of vitamin D levels on bone mineral density and osteoporosis

Abstract: BACKGROUND AND OBJECTIVES:The effects of vitamin D on bone mass remain to be understood. This study was conducted with the objective of evaluating the influence of 25-hydroxyvitamin D (25OHD) levels on bone mineral density (BMD) among Saudi nationals.DESIGN AND SETTING:Cross-sectional study carried out at university hospital from 1 February 2008 to 31 May 2008.SUBJECTS AND METHODS:Healthy Saudi men and women in the peak bone mass (PBM) age group and those aged ≥50 years were recruited from the outpatient depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
54
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 22 publications
3
54
4
Order By: Relevance
“…However, some studies showed contrary findings, as one study by Sadat et al [16] showed a strong association of osteopenia and osteoporosis in patients with vitamin D deficiency though in a smaller cohort than ours [16]. Similarly Bischoff-Ferrari et al [17] also observed a positive correlation between low vitamin D and low BMD in a population of different age groups.…”
Section: Discussionmentioning
confidence: 75%
“…However, some studies showed contrary findings, as one study by Sadat et al [16] showed a strong association of osteopenia and osteoporosis in patients with vitamin D deficiency though in a smaller cohort than ours [16]. Similarly Bischoff-Ferrari et al [17] also observed a positive correlation between low vitamin D and low BMD in a population of different age groups.…”
Section: Discussionmentioning
confidence: 75%
“…Whereas greater bone mass attainment at the time of puberty may provide further bone mass for later cycles of life particularly postmenopausal state [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive correlation between serum vitamin D level and Bone Mineral Density (BMD) in young subjects who are at age of peak bone mass attainment as well as in postmenopausal women [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The main source of calcium in the body is crystals of hydroxyapatite in the bones as well as increasing vitamin D enhances intestinal absorption of calcium; therefore taking supplements of calcium and vitamin D in age of puberty leads to the accumulation of calcium into crystals and increased bone mineral density [25].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen's role in maintaining bone health is far reaching from maintaining calcium homeostasis by stimulating the release of calcitonin and activation of vitamin D (1,25 …”
mentioning
confidence: 99%